Purity and Purification in the Ancient Greek World. Texts, Rituals, and Norms - Carbon, Jan-Mathieu; Peels-Matthey, Saskia (Kernos suppléments, 2018)
Purity, and its converse, impurity, formed a versatile metaphor in the ancient Greek world. Constructing a multifaceted investigation, with both complementary and contrastive approaches, the thirteen papers collected in this volume explore the range of these ideas, from Archaic and Classical Greece to the Roman Near East. Different declensions are readily manifest: purity could be defined as a traditional norm or by institutional law, impurity expressed as a substantive crime or as rhetorical slander. A key debate revolves around the ethical sense of purity and impurity: how early and widely was this notion applied; how did it complement concrete ritual practices of purification and abstention; in other words, in a perspective of continuity and change, how were the inner/mental and outer/corporeal dimensions of purity harmonised ? The present volume celebrates the thirty-fifth anniversary of Robert Parker's seminal work Miasma: Pollution and Purification in early Greek Religion. Analysing a wealth of documents-inscriptions, papyri, literature-both old and new, the authors reveal compelling case-studies, draw out innovative conclusions, and point in fruitful directions for future research. ISBN